Appraising forest diversity in the seasonally dry tropical region of the Gulf of Mexico - Natalia Mesa-Sierra; Federico Escobar; Javier Laborde (Revista Mexicana de Biodiversidad)
Seasonally dry tropical regions in the Neotropics are remarkably biodiverse and provide valuable ecosystem services. Thus, it is crucial to increase and update our information on the biodiversity still preserved within them, particularly in poorly studied areas such as the central coastal plain of the Gulf of Mexico, our study area. A total of 5,583 individuals belonging to 157 species, 113 genera, and 43 families were recorded in 29 forest patches (total sampling area = 8.7 ha). From the floristic composition of these patches, 6 vegetation types were identified: Tropical Dry Oak Forest, Tropical Deciduous Forest, Semi-deciduous Forest, Late Secondary Forest, Intermediate Secondary Forest and Early Secondary Forest. Spatial variation in composition was strongly related to edaphic variables (pH, organic matter, carbon content). Some patches had high local (α) diversity, but even more noteworthy was the distinctively high regional (β) diversity of all the patches together. In spite of the high degree of forest fragmentation in central Veracruz, our results show that it is essential to acknowledge the value of this region to biodiversity and the urgency of developing and implementing protection and management policies that ensure the ecological functions of the landscape and the sustainable development of human activities.